Visual Outcomes, Quality of Vision, Patient Satisfaction and Spectacle Independence After Bilateral Implantation of the Synergy™ Intraocular Lens - De Rojas, Joaquin O; Sandoval, Helga P; Potvin, Richard; Solomon, Kerry D (Clinical ophthalmology (Auckland, N.Z.), 2023)
To evaluate vision, visual quality, patient satisfaction and spectacle independence after bilateral implantation of the TECNIS Synergy™ intraocular lens. Two clinical practices in the USA. Ambispective unmasked non-randomized clinical trial. Patients with a history of uneventful bilateral femtosecond laser assisted cataract surgery with the study IOL implanted, targeted for emmetropia, at least 3 months prior to the study visit were enrolled. Monocular and binocular visual acuity (VA) were measured at distance, intermediate and near, along with binocular mesopic VA. Low contrast binocular VA and reading speed in mesopic and photopic conditions were also measured. Patient satisfaction, spectacle independence, visual symptoms, and functional vision questionnaires were completed. Results from 52 subjects were available for analysis. Mean binocular unaided visual acuity was ~0.1 logMAR (20/20) from distance to 33 cm, with 81% of subjects having 0.2 logMAR (20/25) vision or better at all test distances and 92% reporting never needing glasses at any distance. Average reading speed at 40 cm was only 10 words/minute slower in dim light (p = 0.03). Mesopic and low contrast acuity appeared good. Halos were the most frequent and bothersome visual disturbances, with the greatest effect on driving at night. Eighty-eight percent of subjects reported being "completely" or "mostly" satisfied with their overall unaided vision. This hybrid technology IOL provided a range of binocular visual acuity from distance to 33 cm and good functional vision, even in dim light. Patients should be advised of the likelihood of visual disturbances, particularly halos.